An Eighth-Century b.c.e. Gate Shrine at Tel Lachish, Israel - Ganor, Saʿar (Bulletin of ASOR, 2019)
Excavations conducted on behalf of the Israel Antiquities Authority at Tel Lachish exposed the southern half of the six-chambered gate in Level III. In the eastern chamber, a gate shrine was uncovered. The shrine was split in two: a larger northern room and a smaller southern room. The southern room, which served as the holy of holies, had a niche in its southern wall in front of which a double altar was placed. Dozens of bowls and oil lamps were revealed inside the shrine. At some point, evidently prior to the destruction of Level III by Sennacherib in 701 b.c.e. , the shrine was desecrated and sealed. This act was evident in the breakage of the altar's horns and the placement of a latrine in the holy of holies. The available data suggests that the desecration of the shrine should be associated with Hezekiah's cultic reform (2 Kgs 18:4).